Relationship Between Backpack Use and Positive Early Sign of Scoliosis in Elementary School Student - Illiyin, Shabrina; Karma, Agusni; Triyani; Yunihanawati, Rizan (Poltekkes Kemenkes Jakarta I, 2023)
Background. The use of backpacks that are not suitable both in terms of design, weight of the load, and how to use it can have a negative impact on students due to increased pressure on the spinal structure of adolescents during their growth period. Early detection (scoliosis screening) must be carried out to determine the long-term effects of using the wrong backpack so that treatment can be carried out as soon as possible to avoid the occurrence of more severe musculoskeletal disorders. Aim. Analyzing the relationship between the use of non-ergonomic backpacks on spinal abnormalities (scoliosis) in students Cilandak Barat 08 Elementary School South Jakarta. Method. Analytical quantitative research, by conducting a cross-sectional study simultaneously on individuals of a population at a time. Result. This research found there was no significant relationship between backpack characteristics and the incidence of scoliosis (p-value 1.000) and OR 1.261. It was found that on average the respondents experienced musculoskeletal complaints due to the use of backpacks with non-ergonomic characteristics about 64.8% and scoliosis prevalence about 20.5%. Conclusion. There is no relationship between the characteristics of the backpack with the incidence of scoliosis. The use of a non-ergonomic backpack can still be used by considering the recommended aspects while using it.